Social Network and Small Business Sustainability: A Case Study in Borobudur Temple Tourism Park - Usmawati, Putri; Prasetyo, Yanu Endar; Fedryansyah, Muhammad (E-Journal of Tourism; Volume 8 Number 2 (September 2021), 2021)
This study aims to determine the characteristics and patterns of the social network of souvenir traders in the Borobudur Temple Tourism Park and explore the relationship between social networks and the sustainability of the souvenir merchants’ business. In this qualitative study, researchers conducted data collection (observation and in-depth interview) between January 2018 and January 2019 before the COVID-19 outbreak hit the area. Social network data and information from the interview were analyzed and visualized with the Node-XL computer program. Our findings showed that the formation of a social network of souvenir merchants and small traders was based on kinship, friendship, interests, and contractual relationships. The structures that are maintained and developed in the Borobudur Temple Tourism Park area contain interrelated actors. While the relationship between suppliers and merchants is diagonal, the social interaction and network pattern among small traders in the Borobudur Temple Tourism Park is horizontal. Souvenir merchants and small traders in the Borobudur Temple tourism park are always maintaining their social capital to survive in their business. We can learn that each merchant is closely connected with some key fellow merchants and small or medium traders from this pattern. This network and ties among small traders can also determine trust and social capital between actors. Through each small traders’ social network, a business network based on interest, kinship, friendship, and contractual relationships can be unraveled.